REVITALIZATION OF ISLAMIC EDUCATION IN THE PROPHETIC PERIOD OF MUHAMMAD (610-633 AD) - La Zubair; Zulfi Mubaraq; Mohammad Asrori (Najah Bestari, 2026)
The aim of this research is to understand 3 things: (1) forms, (2) factors, and (3) implications of the research theme. The method used is a library research with a literature review approach. Data collection was carried out using a library research procedure and data analysis techniques using content analysis. The results of the research indicate that, first, the forms (1) purpose: to form a person who is faithful, pious, and has noble morals. (2) material: monotheism, the Qur'an, social, and economic. (3) method: dialogue, parable, demonstration, and story or narrative. (4) mursyid: Prophet Muhammad. (5) students: Khadijah, Ali bin Abi Thalib, Abu Bakar As-Shiddiq, Zaid bin Tsabit, Ummu Aiman. Second, internal factors: the person of the Prophet Muhammad as a good role model and al-Amin (trustworthy). External factors: idol worship and irrational and unusual customs of Arab society. Third, positive implications: many people embraced Islam and the paradigm and customs of Arab society changed. Negative implications: many challenges and sufferings were received by the Prophet Muhammad in realizing the forms and the followers of the Prophet Muhammad were tortured. The conclusion of this research is that various forms, factors, and implications are holistic and religious and relevant to the social context of the time. In addition, this study can be used as a guide in the construction of responsive, progressive and adaptive Islamic history, social and education.